Maternal prepregnancy weight and gestational weight gain in association with autism and developmental disorders in offspring - Matias, Susana L; Pearl, Michelle; Lyall, Kristen; Croen, Lisa A; Kral, Tanja V E; Fallin, Daniele; Lee, Li-Ching; Bradley, Chyrise B; Schieve, Laura A; Windham, Gayle C (Obesity (Silver Spring, Md.), 2021)
Maternal prepregnancy BMI and gestational weight gain (GWG) are examined in relation to autism spectrum disorder (ASD) and other developmental disorders (DD) in offspring in a multisite case-control study. Maternal prepregnancy BMI, obtained from medical records or self-report, was categorized as underweight, normal weight, overweight, obesity Class 1, or obesity Class 2/3. GWG was standardized for gestational age (GWG z score), and the rate (pounds/week) was categorized per adherence with clinical recommendations. Logistic regression models, adjusting for demographic factors, were used to assess associations with ASD (n = 1,159) and DD (n = 1,617), versus control children (n = 1,633). Maternal obesity Class 2/3 was associated with ASD (adjusted odds ratio [AOR] = 1.87, 95% CI: 1.40-2.51) and DD (AOR = 1.61, 95% CI: 1.22-2.13). GWG z score was not associated with DD (AOR = 1.14, 95% CI: 0.95-1.36), but the GWG z score highest tertile was associated with higher odds of ASD, particularly among male children (AOR = 1.47, 95% CI: 1.15-1.88). Results indicate that maternal prepregnancy severe obesity increases risk of ASD and DD in children and suggest high gestational-age-adjusted GWG is a risk factor for ASD in male children. Because maternal BMI and GWG are routinely measured and potentially modifiable, these findings could inform early interventions for high-risk mother-child dyads.